PENDAMPINGAN TEKNIS KELOMPOK TANI MARGO RUKUN DALAM PERANCANGAN JARINGAN IRIGASI AIR TANAH DALAM - Wahyudi, Hari Dwi; Suranto, Much.; Darupratomo; Aini, Syarifah; Ratnanik; Purnomo, Harri; Saputra, Rangga Bagus; Putra, Alif Adilla Kusuma; Arnosy, Muhammad Herlambang Akbar (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2025)
Padukuhan Suru Lor is a part of Kalurahan Hargomulyo, which is located in the Kapanewon Gedangsari, Gunungkidul Regency, Special Region of Yogyakarta. Kalurahan Hargomulyo serves as the administrative center of Kapanewon Gedangsari. The main livelihood of the residents of Padukuhan Suru Lor is farming, and in addition, they are also livestock farmers. The farming in Padukuhan Suru Lor is rain-fed agriculture, which is only effective and productive during the First Rainy Season (MH1). With these conditions, it present a challenge for farmers and agricultural infrastructure observers to provide water for irrigation, especially to overcome the water scarcity problem during the Second Rainy Season (MH2). The expected outcomes after the implementation of this Community Service program are the availability of a technical concept for the deep groundwater irrigation system network, and the construction of a deep groundwater well as a source of water for irrigation in the Deep Groundwater Irrigation System (DGIS) in Padukuhan Suru Lor.